Pola Makan Remaja Sebagai Faktor Risiko Penyakit Gerd - Windi Fahriska Hasibuan; T Aida Larasati; Nabila Aulia Syahdifva Harahap; Belinga Shanel; Revaldo Revaldo; Nabila Nabila (Jurnal Ilmu Kesehatan dan Gizi, 2024)
GERD is a condition in which stomach contents rise back into the esophagus and can even reach the oral cavity, and cause clinical symptoms such as chest pain and irritation of the respiratory tract. GERD is a common clinical problem experienced by millions of people throughout the world, the increasing development of technology, industry, and socio-economic improvements that are increasingly advanced and developing are changing people's behavior and lifestyle, especially teenagers. Following the trend of consuming foods low in nutrition and high in saturated fat is a normal thing for teenagers today. The emergence of GERD can be caused by poor dietary intake, which is not balanced with adequate nutritional sources that a person's body needs. The long-term impact on GERD sufferers that is not treated properly and appropriately can cause serious complications such as inflammation and injury to the esophagus or even increase the risk of esophageal cancer. This data search used the literature review method originating from Google Scholar.